2008
DOI: 10.1098/rstb.2008.0110
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic diversity, molecular phylogeny and biogeography of the rock- and leaf litter-dwelling land snails of Belau (Republic of Palau, Oceania)

Abstract: The endemic diplommatinid land snails (Caenogastropoda: Mollusca) of Belau (Republic of Palau, Micronesia) are an exceptionally diverse group of largely undescribed species distributed among rock and leaf litter habitats on most of Belau's 586 islands. Diplommatinid shell morphology (e.g. shell sculpture) reflects habitat type. In this study, I analysed a subset of the 90 diplommatinid species representing a broad geographical spread of islands in order to reveal the species' phylogenetic relationships and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…Diplommatinidae are generally widely distributed in eastern and southern Asia, northern Australia, the Pacific islands and South America (Páll-Gergely et al 2017). Similarly, Palaina species have been described from localities throughout the western Pacific, Australasia and Southeast Asia (Rundell 2008). Convergent shell morphologies, however, are frequent within Diplommatinidae, which hampers clear generic identifications (Páll-Gergely et al 2017).…”
Section: Material -254 Specimens (Nhmw 2017/0092/0001)mentioning
confidence: 99%
See 2 more Smart Citations
“…Diplommatinidae are generally widely distributed in eastern and southern Asia, northern Australia, the Pacific islands and South America (Páll-Gergely et al 2017). Similarly, Palaina species have been described from localities throughout the western Pacific, Australasia and Southeast Asia (Rundell 2008). Convergent shell morphologies, however, are frequent within Diplommatinidae, which hampers clear generic identifications (Páll-Gergely et al 2017).…”
Section: Material -254 Specimens (Nhmw 2017/0092/0001)mentioning
confidence: 99%
“…Convergent shell morphologies, however, are frequent within Diplommatinidae, which hampers clear generic identifications (Páll-Gergely et al 2017). Molecular phylogenies showed that "Palaina" is non-monophyletic (Rundell 2008, Webster et al 2012). Nevertheless, all phylogenetic studies demonstrated that "Palaina", along with other Diplommatinidae genera like Hungerfordia and Opisthostoma, belongs to geologically young (Miocene or younger) Indo-Pacific and Pacific radiations (Rundell 2008, Webster et al 2012.…”
Section: Material -254 Specimens (Nhmw 2017/0092/0001)mentioning
confidence: 99%
See 1 more Smart Citation
“…The currently recognized subfamilies Diplommatininae and Cochlostomatinae consist of ten Central Indo-Pacific genera with hundreds of species, and a single European genus, respectively (Beesley et al, 1998;Bouchet et al, 2005;Vermeulen, 1993). The subfamilies have been considered separate families on occasion (Fehér, 2004), and the taxonomic structure within the Diplommatininae has been hampered by convergence in shell shape (Rundell, 2008;Solem, 1959;Tillier, 1981;Vermeulen, 1994). Rundell (2008) produced a molecular phylogeny for the three genera found on Belau, viz.…”
Section: Introductionmentioning
confidence: 98%
“…These deal with beetles in Japan (Sota & Nagata 2008), land snails in Belau (Rundell 2008) and the Ogasawara Islands (Davison & Chiba 2008), iguanas in Fiji (Keogh et al 2008), crickets in New Zealand, Australia and New Caledonia (Pratt et al 2008), weevils in the Galápagos (Sequeira et al 2008) and moths in the Galápagos (Schmitz et al 2008) and Hawaii (Rubinoff 2008).…”
mentioning
confidence: 99%